The inhibitory efficacy of Ginsenoside Rg3 on proliferation and migration of colonic carcinoma cells through the JAK3/STAT5 signaling pathway - Xiumei Sun; Han Bi; Feng Gao; Xiaoyu Zhao; Xinyu Feng; Qifu Bo; Jin Liu; Wenhao Wang (Discover Oncology, 2024)
Abstract Objective To elucidate the efficacy of Ginsenoside Rg3 on the reproduction and immigration of HCT-116 cells and its molecular mechanism. Methods Analysis of the cell cycle along with the colony formation assay, and MTT test were performed to detect the effect of Ginsenoside Rg3 (GRg3) on proliferation of HCT-116 cells. Transwell assay and Cell scratch wound method were carried out to determine the impact on the immigration. The differential expressed genes obtained by RNA-sequencing were intersected with the predicted target genes of GRg3, and PPI was constructed to analyze hub genes. The key target gene expression and its downstream genes were evaluated by western blot assay. Results The GRg3 can inhibit the reproduction and immigrating ability of colonic carcinoma cells, decrease the ability of colony formation in HCT-116 cells, and arrest the G2 phase. JAK3 was identified as a key target gene. Western blot assay revealed decreased levels of p-STAT5 and JAK3 post-treatment with Rg3, while STAT5a and STAT5b did not change significantly. Conclusion The GRg3 inhibits the phosphorylation of STAT5 but not the expression of total protein by inhibiting the expression of JAK3, and then inhibits the proliferation and migration of HCT-116 cells. Graphical Abstract